Politics and Trade in Britain, 1776-1914.
1 online resource (l, 212 pages)
Keywords: This volumeexplores the period between Smith⁰́₉s 1776 The Wealth of Nations and ends in the early days of the Anti-Corn Law League campaign on the eve of the 1841 General Election, which prominently featured contrasting commercial policy options between Conservative and Liberal parties. During this period, we witness the growth of free trade sentiment, with opposition to monopolies like the old Chartered Companies, and attempts to create more liberal bilateral commercial treaties. Most importantly, we see the imposition of the protectionist Corn Laws in 1815 at the behest of a Parliament largely based on the landed interest. Between 1815 and 1846, the Corn Laws become the fulcrum of the entire debate on commercial policy, the ⁰́₈keystone in the arch⁰́₉ of the protective system, and slowly, divisions begin to emerge throughout society and between the political parties, culminating in the formation of the Anti-Corn Law League and their attempt to influence politics via ⁰́₈pressure from without⁰́₉. The sources include printed matter such as the diaries of Lord Colchester; various parliamentary papers on commercial policy; printed correspondence of William Pitt, Lord Melbourne, Joseph Sturge; periodical literature from numerous sources such as the Eclectic Review, and The Oriental Herald. Also included is a considerable body of newspaper material from the Manchester Times, Dundee Advertiser, and The Chartist, reflective of the growing importance of the provinces and manufacturing interests in commercial, and local and national politics.